Some Previously Relevant Aspects of Academic Life: Venia Legendi and the Status of a Private Docent in the World and in Riga Polytechnicum (1862–1896) - Baltiņš, Māris (History of Engineering Sciences and Institutions of Higher Education, 2021)
The study examines the status of a private docent, the academic position which was introduced across the world in the 18th century and which also existed in Latvia from the second half of the 19th century until the end of World War II. The status of the private docent as it used to be understood in Latvia is compared with other countries, mainly considering German-type universities. Definition of the terms «venia legendi» and «private docent» providing examples of academic activity of the lecturers of Riga Polytechnicum (RP) allow considering these concepts from various perspectives in order to make their meaning and usage in the previous centuries transparent for the users in the 21st century. Conducting the present research, the author has used archival documents and library collections, the theoretical framework includes the findings of not only the Latvian scientists, but also researchers from Russia, Germany and other countries.